Effect of inoculation and nitrogen top-dressing on yields and fodder value of winter pea cv. Maksimirski ozimi in wheat cv. Sana mixture - Darko Uher; Zvonimir Štafa; Sulejman Redžepović; Mihaela Blažinkov; Sanja Sikora; Dražen Kaučić (Mljekarstvo)
Two year field trials (1999 - 2001) were performed to determine theinoculation seed winter pea and nitrogen top-dressing effect on number and active nodules of pea root and also on the green mass and dry matter yield of winter pea cv. Maksimirski ozimi and wheat cv. Sana mixture. Immediately before sowing the inoculation of pea seeds was accomplished by the indigenous variety of Rhizobium leguminosarum bv. viciae which belongs to the collection of Department of Microbiology at the Faculty of Agriculture University of Zagreb. The highest total nodule number on pea root (159) was determined on the inoculated variant as well as active nodule 144. Average mixture green mass yield were ranging from 24,65 t ha-1 (control) up to 35,50 t ha-1 (inoculation). Total dry matter yields were ranging from 3,93 t ha-1 (control) up to 5,66 t ha-1 (inoculation). Yields crude proteins pea in 2001 were ranging from 692 kg ha-1 (control) up to 1058 kg ha-1 (inoculation) and for wheat, those values ranged from 199 kg ha-1 (control) up to 454 kg ha-1 (nitrogen top-dressing). Total crude proteins mixture yields were in range from 891 kg ha-1 (control) up to 1360 kg ha-1 (inoculation).